Design of rectifier with extended operating input power range. Issue 18 (1st August 2013) - Sun, H.C.; Zhong, Z.; Guo, Y.X.
Abstract : A novel rectifier with a considerably extended operating input power range is presented for wireless power transmission applications. The rectifier utilises a depletion‐mode to enhance the diode's breakdown voltage while its built‐in voltage is preserved. As a result, in comparison with traditional rectifiers, this proposed rectifier can achieve a high RF‐to‐DC conversion efficiency in a much wider input power range. Measurement results show that a conversion efficiency of more than 50% can be obtained over the input power range from − 13.5 to 16.7 dBm, proving that this rectifier is suitable for the wireless power transmission applications with varying input power levels.